LIABILITY REGIME OF ONLINE PLATFORMS NEW APPROACHES AND PERSPECTIVES (EU and comparative law issues and challenges series (ECLIC), 2019)
Collaborative economy creates new business models in different sectors of the economy and produces new impulses for the development and innovations in the traditional areas. However, to answer the new questions arising from this segment of the economy, we must consider the existing legal framework regarding the central subjects of the collaborative economy - online platforms. In this paper we examine one legal aspect of particular relevance in this regard, specifically the liability of online platforms for content that they host. In particular, we consider the existing liability regime of these platforms, new proposals approved by the European Parliament and we conclude this paper with the critical examination of the liability regime in relation to the push for the adoption of voluntary proactive measures on the EU level.